Investigation Of The Effects Of Various Water Mediums On Desulfurization And Deashing Of A Coal Sample By Flotation - F. D. Ayhan (Society for Mining, Metallurgy & Exploration, 2009)
The aim of this study was to investigate the effects of various water mediums on desulfurization and deashing of a coal sample using flotation. For this purpose, experimental studies were conducted on a coal sample containing high ash and sulfur contents. The effects of pH, solid concentration, collector amount and frother amount on the flotation were investigated separately in Mediterranean Sea water, Çermik thermal spring water, snow water and tap water. Flotation results indicated that, when comparing the various water mediums, the following order for the ash content was obtained: snow water < Çermik thermal spring water < tap water < the Mediterranean Sea water. For the reduction of total sulfur, the following order was obtained: snow water > Çermik thermal spring water > Mediterranean Sea water > tap water. When snow water was used as a flotation medium, it was found that a concentrate containing 3.01% total sulfur and 27.64% ash with a total sulfur reduction of 57.06% was obtained from a feed containing 7.01% total sulfur and 41.17% ash.